Clinical decision-making style preferences of European psychiatrists: Results from the Ambassadors survey in 38 countries. Issue 1 (21st October 2022) - Rojnic Kuzman, Martina; Slade, Mike; Puschner, Bernd; Scanferla, Elisabetta; Bajic, Zarko; Courtet, Philippe; Samochowiec, Jerzy; Arango, Celso; Vahip, Simavi; Taube, Maris; Falkai, Peter; Dom, Geert; et al.
Abstract: Background: While shared clinical decision-making (SDM) is the preferred approach to decision-making in mental health care, its implementation in everyday clinical practice is still insufficient. The European Psychiatric Association undertook a study aiming to gather data on the clinical decision-making style preferences of psychiatrists working in Europe. Methods: We conducted a cross-sectional online survey involving a sample of 751 psychiatrists and psychiatry specialist trainees from 38 European countries in 2021, using the Clinical Decision-Making Style – Staff questionnaire and a set of questions regarding clinicians' expertise, training, and practice. Results: SDM was the preferred decision-making style across all European regions ([central and eastern Europe, CEE], northern and western Europe [NWE], and southern Europe [SE]), with an average of 73% of clinical decisions being rated as SDM. However, we found significant differences in non-SDM decision-making styles: participants working in NWE countries more often prefer shared and active decision-making styles rather than passive styles when compared to other European regions, especially to the CEE. Additionally, psychiatry specialist trainees (compared to psychiatrists), those working mainly with outpatients (compared to those working mainly with inpatients) and those working in community mental health services/public services (compared to mixed and private settings) have a significantly lower preference for passive decision-making style. Conclusions: The preferences for SDM styles among European psychiatrists are generally similar. However, the identified differences in the preferences for non-SDM styles across the regions call for more dialogue and educational efforts to harmonize practice across Europe.